2010
DOI: 10.1103/physreva.82.010502
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermochemistry ofK2Rb, KRb2, and

Abstract: The formation and interaction of ultracold polar molecules is a topic of active research. Understanding possible reaction paths and molecular combinations requires accurate studies of the fragment and product energetics. We have calculated accurate gradient optimized ground-state structures and zero-point corrected atomization energies for the trimers and tetramers formed by the reaction of KRb with KRb and corresponding isolated atoms. The K 2 Rb and KRb 2 trimers are found to have global minima at the C 2v c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 43 publications
5
58
3
Order By: Relevance
“…Through detailed electronic structure calculations, they concluded that trimer formation reactions of the type 2XY → X 2 Y + Y are also energetically not allowed for low-lying levels of the singlet state. These results were confirmed by Byrd et al 213,214 who also computed a minimum energy path for the KRb + KRb → K 2 + Rb 2 reaction. It was found that the reaction involves a barrierless path with an intermediate K 2 Rb 2 tetramer at ∼3000 cm −1 below the KRb + KRb and K 2 + Rb 2 asymptotes.…”
Section: E Field-free Reactive Scattering Calculationssupporting
confidence: 79%
See 1 more Smart Citation
“…Through detailed electronic structure calculations, they concluded that trimer formation reactions of the type 2XY → X 2 Y + Y are also energetically not allowed for low-lying levels of the singlet state. These results were confirmed by Byrd et al 213,214 who also computed a minimum energy path for the KRb + KRb → K 2 + Rb 2 reaction. It was found that the reaction involves a barrierless path with an intermediate K 2 Rb 2 tetramer at ∼3000 cm −1 below the KRb + KRb and K 2 + Rb 2 asymptotes.…”
Section: E Field-free Reactive Scattering Calculationssupporting
confidence: 79%
“…Atom-exchange reactions in collisions of heteronuclear alkali metal dimers have received much attention recently. Zuchowski and Hutson, 210 Meyer and Bohn, 211 Quéméner et al, 212 Byrd et al, 213,214 and Tomza et al 215,216 have carried out detailed electronic structure calculations of energetics and reaction paths in these systems. While atom-exchange in KRb + KRb → K 2 + Rb 2 is exoergic, it is not energetically allowed for many other heteronuclear alkali metal dimers in their ground rovibrational level.…”
Section: E Field-free Reactive Scattering Calculationsmentioning
confidence: 99%
“…Therefore, the reaction, if it happens at all, must proceed with an abstraction reaction in which an atom jumps from one molecule to the other. This is exactly the opposite situation from what occurs in KRb, where the exchange is the only possible reaction, and then only just barely [19,23,24]. Second, we find that the Sr-abstraction reaction 2SrF → Sr 2 F + F + E trimer (2) cannot occur at low temperature, whereas the F-abstraction reaction…”
Section: Introductioncontrasting
confidence: 56%
“…In recent work, however, Byrd et al have described the main salient features of this surface [19]. First, along its main reaction coordinate, the reaction presents no energetic barrier to reaction (consistent with the high-reaction rates observed at JILA).…”
Section: Introductionmentioning
confidence: 58%
“…For example, this was seen for Na 2 and K 2 by Zemke et al 9 as well as for the related systems of K 2 +Rb 2 (Ref. 37) and Rb 2 +Cs 2 (Ref. 38), where the lowest energy reaction path was calculated ab initio and indeed was found to be barrierless.…”
Section: Numerical Results and Discussionmentioning
confidence: 77%